1993
DOI: 10.1128/jvi.67.9.5502-5513.1993
|View full text |Cite
|
Sign up to set email alerts
|

Spliced transcripts of human cytomegalovirus

Abstract: The availability of the human cytomegalovirus (HCMV) genomic sequence has resulted in more extensive knowledge of the overall coding capacity of the virus. Using polymerase chain reaction and rapid sequencing techniques, we have studied the splicing of mRNAs from a number of the predicted open reading frames (ORFs). Splicing was found between the UL122(IE2) ORF present within major immediate-early (MIE) region 2 and the downstream ORF (UL118) predicted to encode an incomplete glycoprotein. This locates the IE2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…Taken together, our results show that HHV-6 viruses express three highly abundant lncRNAs, as was shown in other herpesviruses (Gatherer et al, 2011;Hutchinson and Tocci, 1986;Kulesza and Shenk, 2004;McDonough et al, 1985;Rawlinson and Barrell, 1993), and that one of these lncRNAs, lncRNA3, generates a stable non-polyadenylated intronic RNA that appears to be a conserved feature of betaherpesviruses.…”
Section: Previously Unrecognized Hhv-6 Encoded Long Non-coding Rnas (supporting
confidence: 82%
“…Taken together, our results show that HHV-6 viruses express three highly abundant lncRNAs, as was shown in other herpesviruses (Gatherer et al, 2011;Hutchinson and Tocci, 1986;Kulesza and Shenk, 2004;McDonough et al, 1985;Rawlinson and Barrell, 1993), and that one of these lncRNAs, lncRNA3, generates a stable non-polyadenylated intronic RNA that appears to be a conserved feature of betaherpesviruses.…”
Section: Previously Unrecognized Hhv-6 Encoded Long Non-coding Rnas (supporting
confidence: 82%
“…The sequencing results revealed that all 34 cDNA sequences terminated at nt 27543, which is downstream of a poly(A) signal (ATTAAA) at nt 27513-27518. Among the identified cDNA sequences, 25 sequences with lengths from 417 nt to 421 nt began at the region from nt 27040 to nt 27044, which are similar to the spliced UL21.5 transcript reported previously (18). Five sequences with lengths from 765 nt to 1386 nt began from nt 26696 to 26082, which have a similar structure as transcript I (Fig.…”
Section: Ul215 Spliced Transcripts Obtained From the Cdna Librarysupporting
confidence: 72%
“…described (18). The UL21.5 transcript, which consists of a spliced and a non-spliced transcript, was first reported by Rawlinson and Barrell (18) and later re-termed by Bresnahan and Shenk (17).…”
Section: Transcripts With Possible 5' Ends and Structures -----------mentioning
confidence: 99%
“…These include the MCMV ORFs downstream of m123(ie1) and M122(ie3). These ORFs are similar to HCMV UL118, UL117, UL116, and UL115, which have been shown to undergo differential splicing, resulting in 3Ј coterminal transcripts at IE and late times after infection (77,120). Positional or amino acid sequence homologs of HCMV UL115-119 were identified in MCMV, and there were predicted splice sites for the homologs of UL119/118 identified (Table 3).…”
Section: Resultsmentioning
confidence: 92%
“…Transcriptional data are available for differentially spliced transcripts from ORFs M122, m123, and m128 within the MCMV MIE region (42,69,70,88,97). By analogy with HCMV, the MCMV MIE regions ie1, ie2, and ie3 (135) are predicted to extend between positions 165599 (M114) (77,120) and 187296 [M128(ie2)]. The sequence around 700 bp upstream of the m123(ie1) gene (like the homologous region in HCMV) contains a strong enhancer, made up (at least in part) of five 94-bp tandem repeats (Fig.…”
Section: Discussionmentioning
confidence: 99%